The effect of computer aided teaching method on the students' academic achievement in the science and technology course - Bayrak, Beyza Karadeniz; Bayram, Hale (ELSEVIER SCIENCE BV, 2010)
In this study, the effect of computer aided teaching of acid-base subject on the academic achievement science and technology course is investigated. In the material developed by the researcher, it was aimed to enable students learn acid-base subject by using interactive animations and simulations. In order to collect data, a scale consisting of 30 questions was developed by the researcher. As a result of the study, it was found out that teaching of acid-base subject supported with computer aided teaching had a positive effect on the achievements of students in science and technology course.
Keywords: science teaching; science and technology; computer aided teaching; students' achievement; acid-base; INSTRUCTION; Education & Educational Research